Sensitization of TiO2 Thin Film with Different Dye for Solar Cell Application - Sahari, Siti Kudnie; Sawawi, Marini; Kashif, Muhammad; Bahrin, Afiqah; Kemat, Rafidah; Jaafar, Erdawati (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
Titanium Dioxide (TiO2) solution having different concentration were synthesized and deposited on glass substrate by using sol-gel and spin coating method. The effects of structural and electrical properties in Dye-Sensitized Solar Cell (DSSC) application is studied. Recently, TiO2 was studied because it has a major role in the enhancement of electrical properties in DSSC. The starting materials are ethanol, titanium isopropoxide (TTIP), glacial acetic acid (GAA), Triton X-100 and distilled water. The effects of different molarity of TiO2 solution is studied. The solution is then deposited on the substrates by spin coating method to form a transparent TiO2 thin film. The TiO2 thin film is fabricated for DSSC application. The performance of the thin film is characterized by scanning electron microscope (SEM) for structural properties while I-V measurements to analyze the electrical properties of the thin film. It was notified that 0.25 M film has more porous structure. By integrating different dyes with TiO2 thin films it was notified that the turn-on voltage increases from 0.2V to 1.2 for TiO2 and for turmeric, respectively.